A review of productivity in strawberries: marketable yield has a linear, but inconsistent relationship with total yield, and cannot be predicted from total yield. Issue 2 (4th March 2021) - Menzel, Christopher Michael
ABSTRACT: Productivity in strawberry ( Fragaria × ananassa ) can be recorded by measuring marketable or total yield. The first objective of this review was to determine if marketable yield can be predicted from total yield. The second objective of this review was to develop protocols to accurately determine the productivity of strawberry cultivars. Previous research has not examined the relationship between the two measures of productivity and how to best measure the yield of strawberry cultivars. The relationship between marketable and total yield was assessed by examining the performance of strawberry cultivars across 68 studies. Marketable yield had a linear, but inconsistent relationship with total yield across different cultivars, sites and years. The slope from the regression between marketable and total yield ranged from 0.25 to 0.99, with a median of 0.80, and a mean (and SE) of 0.78 ± 0.01. Marketable yield cannot be predicted from total yield. The results of this review demonstrate that marketable yield is a better indicator of productivity than total yield. Both measures of productivity should be used in future cultivar studies. The results also demonstrate that cultivar experiments that include information on the incidence of fruit defects are better than ones that do not.